Teachers' Perception: Self-protection in Children as a Prevention Against Sexual Violence - Fitriana, Siti; Rakhmawati, Ellya; Kusdaryani, Wiwik (KnE Social Sciences, 2024)
The rise in child sexual violence (CSV) cases in Central Java Province worries all levels of society, specifically parents and teachers. Preventive efforts include providing child sexual education, which has been massively promoted by the governments, teachers, and parents to prevent sexual violence against children. The researchers raise the problem of the study “How do kindergarten teachers in Semarang city perceive self-protection as a prevention to CSV?” to explore kindergarten teachers’ perception of self-protection as a tool to prevent CSV. This study used a qualitative method with a phenomenology approach. The participants of the study were classified based on specific criteria. The results showed that self-protection materials, as a prevention to CSV, cover an introduction to body parts in a girl and a boy, sexual relationship knowledge between man and woman, and other knowledge and skills provided to children from an early age. Besides perception, teachers conveyed sexual education materials, including toilet training activities and self-protection materials through movies, videos, songs, and dolls. Sexual education materials adjusted to culture are how to dress, how to speak, and shyness in behavior. Keywords: self-protection, teachers’ perception, child sexual violence, phenomenology